Hypothetical Geological Model Affecting Groundwater Quality in Doabs of Indus Basin, Punjab, Pakistan - Syed Mobasher Aftab; Tahir Maqsood; Abdul Hannan; Saeed Hassan; Abid Raza Zaidi; Ramsha Tahir (International Journal of Economic and Environmental Geology, 2018)
The groundwater quality of Indus Basin around Sargodha and adjacent areas of Punjab Plain is known for its poor-quality in multiple aquifers at different depths. The poor-quality water is being used for domestic and irrigation purposes, causing significant health hazards to communities, ecosystem, livestock, and crops. The aquifer water, sediment analysis, and surface drainage system, including river beds and dormant meanders, have been analyzed during different studies. The subsoil data points had not been concluded or established the geological reason or created a model impacting the quality of groundwater. In the past, limited work has been recognized in multiple source areas and remained focused only to Salt Range outcrops. The geological significance of Kirana-Chiniot Hillocks has not been considered and it has remained to its existing localized exposures. The aquifer solvents support the existence of near to far distance geological formations that are consistently charging the aquifers in Doabs (the area between two rivers). The present study comprises subsurface rock data, composition and geometry below the alluvial cover to speculate geological model which is contributing to alter groundwater composition after dilution and distribution to aquifers. The east-west trending zone of 200-220 km length stretches from Lahore to Khisor Range while its width in the north-south direction is about 60-80 km around Sargodha-Chinot-Sangla Hillocks. The hypothetical model is based on sub-crop rock distribution drilled wells for oil and gas, 2D-Seismic reflection data, regional gravity mapping and geology of Kirana-Chinot-Sangla Hillocks. Cambrian and Precambrian lithologies and associated minerals after dilution with recharging waters are controlling the groundwater quality in Doabs. Keywords: Hypothetical Geological Model, Groundwater Quality, Doab, Indus Basin, Punjab, Pakistan.